Kajian Terhadap Faktor – Faktor Yang Mempengaruhi Subsidi Bahan Bakar Minyak (BBM) Indonesia - Mulyani, Putu Ari; Sudirman, I Wayan; Yuliarmi, Ni Nyoman (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 1, Februari 2015 (pp. 1-112)DO - 10.24843/JEKT.2015.v08.i01.p01, 2015)
This study aims to find out and to analyze the factors that affecting the fuel subsidy (BBM) which written in the state budget. The data has been used in this study as follows secondary data obtained from the records and reports from various agencies such as statistic bureau (BPS), Ministry of Finance, Indonesia bank, the US. Energy Information Administration (EIA), the Ministry of Energy and Mineral Resources, Directorate General of oil and Gas, previous journals and the results of studies. Variables has been analyzed by using path analysis to find out direct and indirect effect as well as Sobel test to find out the level of significance of intervening variable as moderator variable. Test of model validity by using the coefficient of total determination and trimming theory to find out the variation of fuel subsidy (BBM) in Indonesia that it can be explained by the exogen variable. Based on the regression results found the coefficient of total determination 0.998 its means 99.8 percent explained by the model while the remaining 0.2 percent explained by other variables outside of the model. Variable of dollar rate is the dominant variable which directly affects on the fuel subsidy. While the fuel subsidized consumption variable is the dominant variable which indirect effect on fuel subsidies through fuel import. To reduce the burden of fuel subsidy in the future state budget hence the government needs to increase oil lifting to reduce fuel imports by way of exploring new wells to replace the old wells which its lifting is declining and increasing investment in the construction of oil refineries in Indonesia to maintain national energy security as well as trying to develop renewable energy instead of oil as fuel because someday oil as a source of un-renewable energy surely be depleted in number while the man and all their needs would increase from year to year. The government should provide adequate public transportation, thereby reducing private vehicle mobility and most importantly is the government more serious in the implementation of the program of conversion fule to liquid gas for vehicles both in terms of conversion technology and security guarantees for each user of liquid gas.
Keywords: fuel subsidy, state budget, international oil price, fuel consumption